Analyzing cross-talk in mechanomyograhic signals of forearm muscles during grip force task and different wrist postures - Md. Anamul Islam (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2014)
This study analyzed the cross-talk in MMG signals generated by the extensor digitorum (ED), extensor carpi ulnaris (ECU), and flexor carpi ulnaris (FCU) muscles during submaximal to maximal isometric contractions of the grip force (MVIC) and wrist postures of flexion (WF) and extension (WE), and radial (RD) and ulnar (UD) deviations.